Female Sexual Function Index As Sexual Disfunction Predictor On Women Using A Pessary - Setyawan Nurtanio; Andi Rinaldi; R.M. Sonny Sasotya; M. Rizkar Arev Sukarsa; Eppy Darmadi Achmad (Fakultas Kedokteran Universitas Andalas, 2025)
Introduction: Pelvic organ prolapse (POP) is the abnormal descent of pelvic organs that can cause various symptoms, including sexual dysfunction, especially in menopausal women. With increasing life expectancy, the prevalence of POP-related female sexual dysfunction is also rising. Sexual discomfort can result from vaginal wall thinning, stiffness, fatigue, and inability to achieve orgasm, affecting overall well-being and quality of life. Objective: This study aimed to evaluate the improvement in female sexual function using the Indonesian version of the Female Sexual Function Index (FSFI) one week after pessary insertion in both sexually active (SA) and non-sexually active (NSA) women with POP. Methods: A descriptive before-and-after study was conducted on 20 women aged 50–65 years with POP grades II–IV at Al-Ihsan Hospital, Bandung, between November 2023 and January 2024. All subjects received ring pessary treatment. The FSFI questionnaire was administered before and one week after pessary insertion to assess sexual function. Results: Among 20 participants (mean age: 57 years), 16 (80%) reported sexual dysfunction before pessary insertion. After one week, 14 women (70%) were categorized as not having sexual dysfunction, while 6 (30%) remained in the dysfunction group. Of the 16 women initially affected, 11 (68%) experienced improved sexual function. The ring pessary proved effective without negatively affecting sexual activity. Conclusions: Pessary use in women with POP can improve sexual function without adverse effects on sexual intercourse. However, limitations include the small sample size, short follow-up, and use of only one pessary type. Additionally, multiple unmeasured factors, such as biological, cultural, and social factors, can influence outcomes.